A review of the financial costs and benefits of the Roundtable on Sustainable Palm Oil certification: implications for future research - Tey, Yeong Sheng; Brindal, Mark Kennion; Djama, Marcel; Abdul Hadi, Ahmad Hanis Izani; Darham, Suryani (Elsevier, 2021)
In light of growing social and transnational activism against palm oil, governmental, non-government and private sector organizations have begun to advocate a package of sustainable management practices through the Roundtable on Sustainable Palm Oil (RSPO) standard. Since its adoption involves voluntary compliance, understanding the financial costs and benefits is critical. This study reviews the existing literature to identify the financial outcomes associated with RSPO certification. Seventeen analyses qualified. However, only three were considered robust: two revealed positive returns, one negative. While the quality of past research has limited our understanding of the profitability issue, it has provided insights into issues such as incentive and knowledge deficiencies. Comparative research using a standard data template and analytical method is recommended. Given that the standard modifies management practices and that business dynamics affect financial outcomes, it is concluded that research efforts will have to be better tailored for local management.